If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(w + 4) = 2w + -24 Reorder the terms: -2(4 + w) = 2w + -24 (4 * -2 + w * -2) = 2w + -24 (-8 + -2w) = 2w + -24 Reorder the terms: -8 + -2w = -24 + 2w Solving -8 + -2w = -24 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -8 + -2w + -2w = -24 + 2w + -2w Combine like terms: -2w + -2w = -4w -8 + -4w = -24 + 2w + -2w Combine like terms: 2w + -2w = 0 -8 + -4w = -24 + 0 -8 + -4w = -24 Add '8' to each side of the equation. -8 + 8 + -4w = -24 + 8 Combine like terms: -8 + 8 = 0 0 + -4w = -24 + 8 -4w = -24 + 8 Combine like terms: -24 + 8 = -16 -4w = -16 Divide each side by '-4'. w = 4 Simplifying w = 4
| 4y+3=-21 | | 72=9y+36 | | 4(-x-2)+3=15 | | -(-6x+5)=-(x+5) | | (9+7i)/(-10+8i) | | -1+m=-7 | | 3.72x+16=13.8384+4x | | 1/4(2x-3)=7 | | x^4+2x^3-8x=16 | | 16=-4(2x-2) | | b^2+8b-30=3 | | -5/6a=10 | | y=0.14(600)+15.30 | | 1/2/8 | | 600=0.14x+15.30 | | y=0.14x+15.30 | | -7b=49 | | 45=5(y-1) | | 2v-1-5=2 | | (3/2x)+(x/2x-6) | | y-2/9=-6 | | 4(7.65+-2y)+8y=30.6 | | -10-7x=-x-34 | | 8p+7=5p+16 | | P^2=-6p-5 | | a=1/2(3x+2)(4x-5) | | 9n^2+30n-10=0 | | 4x+8y=30.6 | | 2/5/5/4= | | 4x+3x+2x=63 | | 7(x-8)+19=-6 | | 12.3+t=4.7 |